2016
DOI: 10.1093/jac/dkw260
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-dependent colistin hetero-resistance inEnterobacter cloacaecomplex

Abstract: Because the colistin hetero-resistance appeared cluster-dependent in the ECC, it should be advocated to determine the cluster of the strain associated with the infection in parallel with the MIC of colistin. The resistance mechanism may not be similar to other Enterobacteriaceae since only the two-component regulatory system PhoP/PhoQ (and not PmrA/PmrB) seemed to play a role in resistance regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 21 publications
5
79
0
Order By: Relevance
“…Performing a population analysis may not be practical for many laboratories. Heteroresistance to colistin among strains of the Enterobacter cloacae complex is hsp60 genetic cluster dependent (11). There are 12 clusters (C-I to C-XII) of which the species name could be assigned confidently to specific clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a population analysis may not be practical for many laboratories. Heteroresistance to colistin among strains of the Enterobacter cloacae complex is hsp60 genetic cluster dependent (11). There are 12 clusters (C-I to C-XII) of which the species name could be assigned confidently to specific clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, colistin heteroresistance in E. cloacae 146 was induced by innate immune defenses within a murine infection model to lead to treatment 147 failure (40). Transcriptional analysis of susceptible and resistant populations suggested that pEtN 148 and L-Ara4N lipid A modifications contribute to heteroresistance (40) and PhoPQ contributed to 149 regulation (35,40), as described in other Enterobacteriaceae (5). However, it was not established 150 that the lipid A modifications actually occur, nor has PhoPQ-dependent, PmrAB-independent 151 regulation of colistin heteroresistance been fully described in E. cloacae or other ECC isolates.…”
Section: Introductionmentioning
confidence: 93%
“…infections have increasingly emerged in nosocomial settings and are problematic because they 135 encode multidrug resistance (MDR) mechanisms, which limits treatment options (33, [35][36][37]. 136…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations